2017
DOI: 10.1016/j.amepre.2017.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Cooking at Home: A Strategy to Comply With U.S. Dietary Guidelines at No Extra Cost

Abstract: Introduction Cooking at home is associated with better diet quality. This study examined the frequency of home-cooked dinners versus eating out in relation to the Healthy Eating Index (HEI), and food expenditures. Methods The Seattle Obesity Study used a stratified random sample of 437 King County adults. In-person computer-assisted interviews collected sociodemographic and behavioral data during 2011–2013. HEI-2010 and 2005 were computed using Food Frequency Questionnaires. Multivariable regression analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
87
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(101 citation statements)
references
References 45 publications
7
87
1
6
Order By: Relevance
“…Christensen and Carpiano also examined the effect of specific types of network social capital (measures of social involvement related to employment, apprenticeship, child education and residence) and found that social capital was both positively and negatively associated with BMI and that this relationship was mediated through greater participation in sports and strenuous exercise (lower BMI) and greater interest in cooking (higher BMI) . While the positive association of social capital and BMI through interest in cooking may seem counterintuitive (home cooking has been associated with lower BMI and eating out increases the risk of obesity ), the authors explain their findings in terms of (i) a greater desire to entertain friends as opposed to preparing healthy and nutritious meals and (ii) the receipt of greater demands from others, resulting in preparing meals for oneself and others that are more convenient and time efficient than healthy. Various researches have pointed out how cooking interest, sometimes driven by the massive increase in TV cooking shows that promote fancy rather than healthy meals, can also explain this association .…”
Section: Resultsmentioning
confidence: 99%
“…Christensen and Carpiano also examined the effect of specific types of network social capital (measures of social involvement related to employment, apprenticeship, child education and residence) and found that social capital was both positively and negatively associated with BMI and that this relationship was mediated through greater participation in sports and strenuous exercise (lower BMI) and greater interest in cooking (higher BMI) . While the positive association of social capital and BMI through interest in cooking may seem counterintuitive (home cooking has been associated with lower BMI and eating out increases the risk of obesity ), the authors explain their findings in terms of (i) a greater desire to entertain friends as opposed to preparing healthy and nutritious meals and (ii) the receipt of greater demands from others, resulting in preparing meals for oneself and others that are more convenient and time efficient than healthy. Various researches have pointed out how cooking interest, sometimes driven by the massive increase in TV cooking shows that promote fancy rather than healthy meals, can also explain this association .…”
Section: Resultsmentioning
confidence: 99%
“…As indicated by Farfan et al (2017) in their findings, the consumption of food particularly for FAFH is rapidly growing across the developing world, and will continue to do so as GDP per person grows and food systems evolve. Interestingly, Tiwari et al (2017) found that income is unrelated with consuming food at home.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most of the previous studies indicated that household size or family size is one of the important variables used to determine household expenditure and is statistically significant (Benus et al, 1976;Battese & Bonyhady, 1979;Kulub Abd. Rashid et al, 2010;Sekhampu & Niyimbanira, 2013;Tiwari et al, 2017). For FAFH, Lee and Tan (2007) found that household size did not affect total monthly household expenditure on FAFH.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, people who cook at home more often, rather than eating out, tend to have healthier overall diets without higher food expenses. In addition, they perform significantly better on the HEI and were less likely to be obese (Tiwari et al., )…”
mentioning
confidence: 99%